Analisis Kinerja Keuangan Sebagai Dasar Investor Dalam Menanamkan Modal Pada PT. Bukit Asam,TBK (Study Kasus pada PT. Bukit Asam,TBK) - Farida Efriyanti; Retno Anggraini; Yunus Fiscal (Universitas Bandar Lampung (UBL), 2012)
Researchers conducted the study on PT. Bukit Asam Tbk, a company engaged in coal. In running the business of PT. Bukit Asam Tbk facing problems in measuring the achievements of the company based on the financial ratios of liquidity, solvency, activity and profitability. Over the last three years ie during the years 2009-2011. Rumussn problem is: